Inhibition of CX3CL1 by treadmill training prevents osteoclast-induced fibrocartilage complex resorption during TBI healing - Liu, Xiao; Zhou, Mei; Tan, Jindong; Ma, Lin; Tang, Hong; He, Gang; Tao, Xu; Guo, Lin; Kang, Xia; Tang, Kanglai; Bian, Xuting (Frontiers in Immunology, 2024)
Introduction The healing of tendon-bone injuries is very difficult, often resulting in poor biomechanical performance and unsatisfactory functional recovery. The tendon-bone insertion has a complex four distinct layers structure, and previous studies have often focused on promoting the regeneration of the fibrocartilage layer, neglecting the role of its bone end repair in tendon-bone healing. This study focuses on the role of treadmill training in promoting bone regeneration at the tendon-bone insertion and its related mechanisms. Methods After establishing the tendon-bone insertion injury model, the effect of treadmill training on tendon-bone healing was verified by Micro CT and HE staining; then the effect of CX3CL1 on osteoclast differentiation was verified by TRAP staining and cell culture; and finally the functional recovery of the mice was verified by biomechanical testing and behavioral test. Results Treadmill training suppresses the secretion of CX3CL1 and inhibits the differentiation of local osteoclasts after tendon-bone injury, ultimately reducing osteolysis and promoting tendon bone healing. Discussion Our research has found the interaction between treadmill training and the CX3CL1-C3CR1 axis, providing a certain theoretical basis for rehabilitation training.